Cordia Dichotoma: A Comprehensive Review of its Phytoconstituents and Endophytic Fungal Metabolites and their Potential Anticancer Effects - Patil, Saurav M.; Bhattacharya, Sankha (Current Topics in Medicinal Chemistry, 2024)
Cordia Dichotoma is a valuable medicinal plant belonging to the family Boraginaceae. It consists of several beneficial secondary metabolite components, including alkaloids, carbohydrates, flavonoids, glycosides, saponins, and tannins. Numerous studies have been conducted to assess the anticancer properties of Cordia Dichotoma on MCF-7, A-549, PC3, and HeLa cancer cell lines, primarily utilizing ethanolic extract, methanolic extract, and chloroform extract. The results of these studies have demonstrated significant effects. Furthermore, several studies have revealed the rich phytoconstituent content of Cordia Dichotoma with some significant components previously utilized by researchers to investigate the anticancer properties of specific compounds. This review discusses several of these components, including β-sitosterol, α-amyrin, Quercitrin, Robinin, betulin, Taxifolin, and Hesperetin. Additionally, a recent study uncovered that the anticancer effect of metabolites from endophytic fungi residing on the Cordia Dichotoma plant is attributed to a property of the plant itself. This review focuses on the current state of anticancer research related to this plant and its components.
Keywords: Robinin